Leishmanial Hepatitis with Chronic Hepatitis B Infection Treated Successfully with Liquid Form of Liposomal Amphotericin B - A Case Report - Salma, Umma; Khan, Abed Hussain; Rahaman, Mohammad Ferdous Ur; Irshadullah, Naseeb Muhammad; Shumy, Farzana; Chowdhury, M A Jalil (Bangabandhu Sheikh Mujib Medical University Journal, 2012)
Hepatic involvement either due to leishmaniasis or due to coexisting viral infection sometime poses a problem for the clinicians. Atypical presentation is also challenging for them. We present a case of visceral leishmaniasis (Kala-azar) from a non endemic zone, co infection with hepatitis B virus simulating chronic viral hepatitis successfully treated with liquid form of liposomal amphotericin B. DOI: http://dx.doi.org/10.3329/bsmmuj.v5i1.11018 BSMMU J 2012; 5(1):55-56